1999
DOI: 10.1161/01.cir.100.suppl_2.ii-351
|View full text |Cite
|
Sign up to set email alerts
|

RSR13, a Synthetic Allosteric Modifier of Hemoglobin, Improves Myocardial Recovery Following Hypothermic Cardiopulmonary Bypass

Abstract: Background-During hypothermic blood cardioplegia, oxygen delivery to myocytes is minimal with ineffective anaerobic metabolism predominating. RSR13,[2][3][4]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…All animals with increased P 50 subjected to global ischemia and cardiopulmonary bypass returned to normal sinus rhythm and doubled CO (22). Right shifting the ODC also improved the recovery of stunned myocardium (32), reduced anemia-induced brain damage (12), and improved neurological outcome from brain ischemia (27).…”
Section: Discussionmentioning
confidence: 99%
“…All animals with increased P 50 subjected to global ischemia and cardiopulmonary bypass returned to normal sinus rhythm and doubled CO (22). Right shifting the ODC also improved the recovery of stunned myocardium (32), reduced anemia-induced brain damage (12), and improved neurological outcome from brain ischemia (27).…”
Section: Discussionmentioning
confidence: 99%
“…When such an agent becomes available, there are a myriad of both cardiac and general surgical applications that go far beyond simply that of a 'blood substitute.' phenoxy]2-methylpropionic acid) a synthetic allosteric modifier of hemoglobin (reproduced from Kilgore et al, [60] with permission).…”
Section: Resultsmentioning
confidence: 99%
“…[61] More importantly, RSR13 has been shown to increase brain oxygen tension and reduce infarct size in a cat model of stroke, [59] and to reduce cell damage, when given at reperfusion, in a rat model of global cerebral ischemia. [60] In a canine model of global myocardial ischemia during CPB, RSR13 improved myocardial function when given at reperfusion. [60] …”
Section: Global and Focal Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we have previously shown that, although RSR13 does not provide independent neuroprotection from a focal ischemic insult (33), when combined with other pharmacotherapy (e.g., dizocilpine), an increase in P 50 serves to reduce ischemic brain damage in normothermic animals (27). RSR13 also has been shown to augment hypothermic protection of the myocardium in a canine cardiopulmonary bypass model (25). As a result, we speculated that RSR13 might also enhance the neuroprotection provided by hypothermia.…”
Section: Discussionmentioning
confidence: 98%